2020
DOI: 10.3390/jcm9113424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Visibility of Fetal Tooth Buds on 1.5 and 3 Tesla MRI

Abstract: Dental anomalies coincide with genetic disorders, and prenatal identification may contribute to a more accurate diagnosis. The aim of this study was to assess whether fetal Magnet Resonance Imaging (MRI) is suitable to visualize and investigate intrauterine dental development in the upper jaw, and to compare the quality of visibility of tooth buds between 1.5 Tesla (T) and 3T images. MR images of fetuses Gestational Week (GW) 26.71 ± 4.97 from 286 pregnant women with diagnoses unrelated to dental anomalies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Eruption sequences are fairly consistent and well-documented in the literature but are beyond the scope of this article [ 25 , 26 ]. All primary tooth germs and first permanent molar tooth germs are detectable by MRI at birth [ 27 ]. It is important to note, however, that at birth, none of the teeth are erupted into the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Eruption sequences are fairly consistent and well-documented in the literature but are beyond the scope of this article [ 25 , 26 ]. All primary tooth germs and first permanent molar tooth germs are detectable by MRI at birth [ 27 ]. It is important to note, however, that at birth, none of the teeth are erupted into the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Zemet (2020), Gai (2022), Arangio (2013) and co-authors, confirmed the added diagnostic value of fetal MRI for evaluation of fetal craniofacial anomalies in retrospective studies comparing MRI and US [10][11][12]. Other studies have focussed on the MRI imaging of specific features, pathology and measurements within the craniofacial anatomy, for example; the orbits [13][14][15]; orofacial clefts, including cleft lip and palate [16][17][18][19][20][21]; inner, middle and external ear structures [22][23][24][25]; the upper and lower jaw [26][27][28]; and skull shape deformities to include craniosynostosis [29][30][31]. Due to the relative rarity of craniofacial malformations, most fetal MRI studies are retrospective in nature, consist of case series studies, and there are a lack of control subjects to assess diagnostic accuracy in a clinical setting.…”
Section: Mri Of Fetal Craniofacial Featuresmentioning
confidence: 86%
“…Zemet (2020), Gai (2022), Arangio (2013) and co-authors, confirmed the added diagnostic value of fetal MRI for evaluation of fetal craniofacial anomalies in retrospective studies comparing MRI and US [10][11][12]. Other studies have focussed on the MRI imaging of specific features, pathology and measurements within the craniofacial anatomy, for example; the orbits [13][14][15]; orofacial clefts, including cleft lip and palate [16][17][18][19][20][21]; inner, middle and external ear structures [22][23][24][25]; the upper and lower jaw [26][27][28]; and skull shape deformities to include craniosynostosis [29][30][31]. Due to the relative rarity of craniofacial malformations, most MRI studies are retrospective in nature, consist of case series and case studies, and there is a lack of control subjects to assess diagnostic accuracy in a clinical setting.…”
Section: Introductionmentioning
confidence: 86%